KAJIAN PERTUMBUHAN VEGETATIF TANAMAN PADI (Oryza sativa L.) TERHADAP PEMBERIAN BERBAGAI DOSIS AZOLLA - Arum Asriyanti Suhastyo (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2022)
Azolla is an organic material wealthy in nutrients, particularly nitrogen, required for lowland rice. The employment of Azolla as fertiliser for rice doesn’t ought to be costly and might even suppress weed growth. This study aimed to see the most effective application of Azolla to rice growth. The analysis technique used was a Randomized Block Style Design (RAKL) with a pair of treatments being tried. The treatment of 1 dose of Azolla consisted of a dose of Azolla 0 (A1), Azolla 30 g/bucket(A2) and a dose of Azolla 45 g/bucket. (A3). Treatment 2 was immersion consisting of immersion (B1) and no immersion (B2). Azolla was applied 2 times, half the dose 1 week before planting and 10 days after planting. Every treatment was recurrent 5 times thus there were 30 experimental treatments. The data were analyzed using the F test, if it was significantly different, it was followed by Duncan's test (DMRT) at a 5% level. The result of this research is that Azolla dose treatment and immersion have not been able to increase plant height and the number of tillers.Keywords: Azolla, fertilizer, paddy